Properties of standing balance control under noisy galvanic vestibular stimulation - Sonobe, Motomichi; Mitsutake, Tsubasa (Frontiers in Neurology, 2025)
Vestibular sensation contributes to balance control during standing as well as somatosensation and vision. Previous studies have indicated that noisy galvanic vestibular stimulation (nGVS) activates vestibular function and improves standing balance in many subjects. However, the mechanism for improving balance control with the addition of nGVS remains unclear. This study aimed to clarify the balance control mechanism improved by nGVS using detailed motion data during quiet standing. Thirty-two young healthy subjects performed quiet standing tests for 40 s with their eyes closed under sham and optimal intensity stimulation. Detailed data consisting of the center of mass (COM) displacement and acceleration of the body, head acceleration, and lower and upper body accelerations were obtained from measurements using a force platform and a head inertial sensor based on the equations of motion of rigid body models. In addition, our study discusses the contributions of joint strategies for COM control and head acceleration control. The contributions of the ankle and hip strategies were calculated from the COM accelerations of the lower and upper bodies. The results indicated that the more effective group of nGVS suppressed head acceleration using the ankle strategy in the anteroposterior direction. This implies that acceleration feedback from vestibular function affects the quality of the ankle joint strategy control. The findings of this study could contribute to the evaluation of vestibular sensory weighting during standing and development of intervention methods for vestibular function using nGVS.